2022
DOI: 10.3389/fgene.2022.1039440
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis of the prognostic and immunological roles of DEAD-box helicase 5 (DDX5) in human tumors

Abstract: Background: Recent studies have demonstrated the significance of the DEAD-box helicase 5 (DDX5) gene, which is involved in pathways concerning the modification of RNA structures. DDX5 functions as a coregulator of cellular transcription and splicing, and participates in the processing of small noncoding RNAs. The aberrant regulation of DDX5 expression possibly plays a significant role in the genesis of cancer. However, there are no comprehensive pan-cancer studies on DDX5. This study is the first to conduct a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Liu et al performed a comprehensive pan-cancer analysis of the prognostic and immunological roles of DDX5 in human tumors [ 111 ]. The analysis revealed that the DDX5 mRNA increase in tumors is related to decreased overall survival (OS), progression-free interval (PFI), and disease-specific survival (DSS) in 3 cancers but increased OS, PFI, and DSS in others [ 111 ]. While this is important information, it should be recognized that mRNA may not always reflect the protein situation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al performed a comprehensive pan-cancer analysis of the prognostic and immunological roles of DDX5 in human tumors [ 111 ]. The analysis revealed that the DDX5 mRNA increase in tumors is related to decreased overall survival (OS), progression-free interval (PFI), and disease-specific survival (DSS) in 3 cancers but increased OS, PFI, and DSS in others [ 111 ]. While this is important information, it should be recognized that mRNA may not always reflect the protein situation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies indicated that degradation of DDX5 (protein) by FL118 induces cancer cell apoptosis but at the same time induces DDX5 mRNA levels [ 46 ]. The other 3 major findings by Liu et al’s analyses include (i) methylation in the DDX5 promoter is significantly reduced in 8 cancer types [ 111 ]; (ii) DDX5 is associated with multiple cellular pathways (e.g., RNA splicing, Notch signaling, and viral carcinogenesis) [ 111 ]; and (iii) DDX5 mRNA expression is highly correlated with the infiltration of CD8( +) T cells, cancer-associated fibroblasts (CAFs), and B cells in a wide variety of malignancies [ 111 ]. The Li et al’s last finding in their pan-cancer analysis of DDX5 mRNA appears to be inconsistent with the potential role of DDX5 (protein) in immune suppression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEAD-box polypeptide 5 (DDX5) belongs to the DEAD-box RNA helicase family, the members of which utilize the energy derived from ATP hydrolysis to unwind doublestranded RNA (dsRNA) molecules [4]. DDX5 is a multifunctional protein and participates in numerous cellular processes, including mRNA splicing, mRNA export and translation, and ribosome and miRNA bioDDX5sis [5].…”
Section: Introductionmentioning
confidence: 99%